1994
DOI: 10.1007/bf00971333
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of avian N-methyl-d-aspartate receptor type1 (NMDA-R1) gene

Abstract: Birds have several advantages in the study of memory formation, as imprinting and passive avoidance behaviors in chick are often used as model systems. However, the primary structure of the bird N-methyl-D-aspartate (NMDA) responsive glutamate receptor, which is assumed to play a critical role in memory formation, has not been determined. In this report we describe the cDNA cloning of a subunit of NMDA receptors (NMDA-R1) from duck and analysis of its structure and distribution in the brain. The N-terminal 898… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…The sequence comparison of the Apteronotus NR1 protein segment with homologous segments from rat, human, and duck. The fish sequence begins at a position that is homologous to that of amino acid 48 of the rat (Anantharam et al, 1992) and duck (Kurosawa et al, 1994) sequences and that of amino acid 53 of the human sequence (Planells-Cases et al, 1993). Boxes indicate residues that are identical in two or more sequences, and numbers indicate the amino acid positions.…”
Section: Isolation Of the A Leptorhynchus Nmdar1 Partial Cdnamentioning
confidence: 99%
“…The sequence comparison of the Apteronotus NR1 protein segment with homologous segments from rat, human, and duck. The fish sequence begins at a position that is homologous to that of amino acid 48 of the rat (Anantharam et al, 1992) and duck (Kurosawa et al, 1994) sequences and that of amino acid 53 of the human sequence (Planells-Cases et al, 1993). Boxes indicate residues that are identical in two or more sequences, and numbers indicate the amino acid positions.…”
Section: Isolation Of the A Leptorhynchus Nmdar1 Partial Cdnamentioning
confidence: 99%
“…First, functional NMDA receptors cannot form in the absence of the NMDAR1 subunit, and physiological and ligand binding studies demonstrate the presence of functional NMDA receptors in turtles [Young et al, 1990;Larson-Prior et al, 1991;Blanton and Kriegstein, 1992]. Secondly, an NMDAR1 subunit has been demonstrated in chick [Kurosawa et al, 1994] and in a lizard species [Rodger et al, 1999], as well as in Xenopus laevis and a teleost species [Soloviev et al, 1997;Dunn et al, 1998]. Thus, it seems highly unlikely that turtles would possess NMDA receptors lacking an NR1 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, because functional NMDA receptors cannot form without the NMDAR1 subunit [Seeburg, 1993;Hollman and Heinemann, 1994], because functional NMDA receptors have been demonstrated in turtle nervous system by electrophysiological means [Larson-Prior et al, 1991;Blanton and Kriegstein, 1992] and because an NR1 subunit has been demonstrated in an avian species [Kurosawa et al, 1994] and in a lizard species [Rodger et al, 1999], it seems likely that NMDAR1 subunits are present in turtle brain. Our failure to detect these subunits with a monoclonal antibody directed against rat NMDAR1 seems likely to reflect the fact that the NMDAR1 epitope against which this antibody is directed is sufficiently different in turtles that the antibody against a mammalian NMDAR1 does not recognize turtle NMDAR1.…”
Section: Methodsmentioning
confidence: 99%
“…Recently biochemical studies have shown that these three receptors are pentameric complexes ) composed of selected subunits of different kinds (Brose et al, 1994) but structurally homologous: GluR1-4 for AMPA receptors (Hollmann et al, 1989;Keinanen et al, 1990), GluR5-7 and KA1-2 for kainate receptors (Egebjerg et al, 1991;Werner et al, 1991;Bettler et al, 1992;Herb et al, 1992) and NR1-2 for NMDA receptors (Moriyoshi et al, 1991;Monyer et al, 1992). The AMPA receptors (Ottiger et al, 1995) and some NMDA subunits (Kurosawa et al, 1994;Basham et al, 1999) have been (partially) cloned in birds, but, to our knowledge, kainate receptors have never been cloned nor purified in any avian species. A kainate-binding protein (KBP) with high sequence homology to the mammalian kainate receptor has however been cloned in chicken.…”
mentioning
confidence: 98%
“…In birds, a few studies have characterized the binding and/or sequence of several types of glutamate receptors (Bowie and Smart, 1994;Kurosawa et al, 1994;Ottiger et al, 1995;Lowe et al, 1997;Jacobsson et al, 1998;Basham et al, 1999). The distribution of the receptor subunits GluR1-4 has been studied in the pigeon by in situ hybridization (Ottiger et al, 1995) and by immunocytochemistry (Ottiger et al, 1995).…”
mentioning
confidence: 99%